Genome-Wide Analysis Reveals Hypoxic Microenvironment Is Associated With Immunosuppression in Poor Survival of Stage II/III Colorectal Cancer Patients - Chen, Yu-feng; Yu, Zhao-liang; Lv, Min-yi; Zheng, Bin; Tan, Ying-xin; Ke, Jia; Liu, Xuan-hui; Cai, Ze-rong; Zou, Yi-feng; Lan, Ping; Wu, Xiao-jian; Gao, Feng (Frontiers in Medicine, 2021)
Background: Hypoxia is associated with a poorer clinical outcome and resistance to chemotherapy in solid tumors; identifying hypoxic-related colorectal cancer (CRC) and revealing its mechanism are important. The aim of this study was to assess hypoxia signature for predicting prognosis and analyze relevant mechanism. Methods: Patients without chemotherapy were selected for the identification of hypoxia-related genes (HRGs). A total of six independent datasets that included 1,877 CRC patients were divided into a training cohort and two validation cohorts. Functional annotation and analysis were performed to reveal relevant mechanism. Results: A 12-gene signature was derived, which was prognostic for stage II/III CRC patients in two validation cohorts [TCGA, n = 509, hazard ratio (HR) = 2.14, 95% confidence interval (CI) = 1.18 – 3.89, P = 0.01; metavalidation, n = 590, HR = 2.46, 95% CI = 1.59 – 3.81, P < 0.001]. High hypoxic risk was correlated with worse prognosis in CRC patients without adjuvant chemotherapy (HR = 5.1, 95% CI = 2.51 – 10.35, P < 0.001). After integration with clinical characteristics, hypoxia-related gene signature (HRGS) remained as an independent prognostic factor in multivariate analysis. Furthermore, enrichment analysis found that antitumor immune response was suppressed in the high hypoxic group. Conclusions: HRGS is a promising system for estimating disease-free survival of stage II/III CRC patients. Hypoxia tumor microenvironment may be via inhibiting immune response to promote chemoresistance in stage II/III CRC patients.